The East African Community : Prospects for Sustained Growth - McAuliffe, Catherine; Saxena, Sweta; Yabara, Masafumi (Washington, D.C. : International Monetary Fund, 2012)
The East African Community (EAC) has been among the fastest growing regions in sub-Saharan Africa in the past decade or so. Nonetheless, the recent growth path will not be enough to achieve middle-income status and substantial poverty reduction by the end of the decade-the ambition of most countries in the region. This paper builds on methodologies established in the growth literature to identify a group of countries that achieved growth accelerations and sustained growth to use as benchmarks to evaluate the prospects, and potential constraints, for EAC countries to translate their recent growth upturn into sustained high growth. We find that EAC countries compare favorably to the group of sustained growth countries-macroeconomic and government stability, favorable business climate, and strong institutions-but important differences remain. EAC countries have a smaller share of exports, lower degree of financial deepening, lower levels of domestic savings, higher reliance on donor aid, and limited physical infrastructure and human capital. Policy choices to address some of these shortcomings could make a difference in whether the EAC follows the path of sustained growth or follows other countries where growth upturns later fizzled out.a.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet